Digital Initiatives for Sustainability and Workforce Development at Grigol Robakidze University - Kadagidze, Lamara (European Scientific Journal, ESJ, 2025)
In an era defined by rapid technological advancement and digital transformation, educational institutions play a crucial role in preparing a workforce that is not only skilled but also adaptable to the evolving demands of the global economy. In Georgia, this challenge has become increasingly evident, prompting significant reforms within the education system. Central to these reforms is the Unified National Strategy of Education and Science of Georgia (2022-2030), which emphasizes sustainability, digital transformation, and inclusivity as key components of educational development. The present article explores the initiatives undertaken by Grigol Robakidze University (GRUNI) to foster sustainable workforce development through digital competencies. It highlights the pivotal role of the GRUNI Sustainable Development Goals (SDGs) Center in promoting sustainability through innovative educational projects and various interdisciplinary workshops. The university’s commitment to enhancing career readiness is demonstrated through activities like employment fairs, partnerships with industry leaders, and specialized training programs. Furthermore, the paper examines how GRUNI’s endeavors align with the goals of the national strategy, particularly in addressing the need for digital literacy among future alumni and educators. By integrating successful practices from Western examples, GRUNI aims to advance workforce preparedness and contribute to a sustainable future. The present article employs a comprehensive literature review methodology, analyzing academic studies, institutional reports, and policy documents to explore the initiatives undertaken by GRUNI to foster sustainable workforce development through digital competencies. The study synthesizes data from GRUNI’s project reports, international collaborations, and educational programs, providing insights into the university’s approach to integrating digital literacy and sustainability into its curricula. The findings emphasize the importance of collaborative efforts between educational institutions and industry stakeholders to ensure that graduates are equipped to meet the demands of the modern workforce. The article concludes by proposing strategies to incorporate best practices into GRUNI’s ongoing efforts and strengthen partnerships with industry, while also reflecting on how educational reforms can support economic stability, growth, and the development of a digitally skilled and sustainable workforce in Georgia.